Isolation of adipose stem cells from human skin adipose tissue - Mohamed, Mohaini (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2009)
Traditionally, stem cells are isolated from bone marrow. These cells have the potency to develop into various types of cells. Thus, mesenchymal stem cells from bone marrow can be used in treating the diseases that need cells therapies or regenerative of cells. Much of the procedures that involve the aspiration of stem cells from bone marrow were invasive and painful. Thus, many researches try to find the alternative source of stem cells. Adipose tissue which is ubiquitous in human body and can be easily isolated promise as a novel source for tissue engineering and regenerative medicine. When compared with bone marrow stem cells, adipose-derived stem cells may develop into adipocytes, chondrocytes, osteocytes and myocytes in vitro. In this research project, adipose tissues from humans were collected and isolated in vitro. The isolation procedures involved centrifugation, filtration and culturing with DMEM: F-12 (1:1), FBS and PenStrep. Adipose stem cells were isolated from human subcutaneous adipose tissue, and appeared as fibroblast-like morphology observed under inverted phasecontrast microscope.